Anthropometry and somatotype of pre-adolescent soccer players: Comparisons amongst elite, sub-elite and non-elite players with non-players - Bidaurrazaga-Letona, I.; Zubero, J.; Lekue, J. A.; Amado, M.; Gil, S. M. (Collegium Antropologicum, 2016)
The aim of the present study was to compare the anthropometry and somatotype of pre-adolescent soccer players of a wide range of levels and ages, and boys of the general population, in order to define the most relevant anthropometric characteristics related to success and promotion to youth soccer elite levels. To this end, 528 youngsters (11.9±0.3 years) divided in four different age groups (Under-11, Under-12, Under-13 and Under-14) and four different training levels (elite, sub-elite and non-elite soccer players, and the general population) were compared. Height, body mass, skinfolds, and limb diameters and circumferences were measured. Moreover, body composition and somatotype were calculated. To determine the differences between the training groups in each age group, the effect size (Cohen`s d) was calculated. Elite players were significantly taller than the rest of the players across all ages (d=0.30-1.18). In the Under-11 group, elite players were lighter than sub-elite players and the general population (d=0.30-0.54) but, as age increased, elite players became heavier than players in the rest of the groups (d=0.28-0.87). Also, our findings indicate that elite players had the lowest BMI (d=0.21-0.84), and the smallest limb diameters (d=0.24-1.19) and circumferences (d=0.22-0.96) across all ages. In addition, elite and sub-elite players had significantly lower values of skinfolds (d=0.21-2.18) and, the lowest fat (d=0.24-1.35) and the highest muscle (d=0.40-1.47) percentages. Finally, while mesomorphy was the major component in elite and sub-elite players (d=0.27-0.89), non-elite players and the general population presented higher levels of endomorphy (d=0.72-2.21). The present study supports the idea that young soccer players are bigger and leaner than their age counterparts who never engaged in regular sporting activity. Moreover, high fat percentage appeared to be a negative factor related to the selection of players.